Respostas
respondido por:
1
3m2 - 6mn ; 12m2 - 48n2 ; m2 -4mn +4n2
3m2 - 6mn = 3m( m - 2n)
12m2 - 48n2 = 12(m2 - 4n2) ==> 2.2.3(m + 2n)(m - 2n)
m2 -4mn +4n2 = (m - 2n)2
MMC = 2.2.3(m + 2n)(m - 2n)2 ==> 12(m + 2n)(m - 2n)2
==================================================
3m2 - 6mn ; 12m2 - 48n2 ; m2 -4mn +4n2
3m2 - 6mn = 3m( m - 2n)
12m2 - 48n2 = 12(m2 - 4n2) ==> 12(m + 2n)(m - 2n)
m2 -4mn +4n2 = (m - 2n)2
MDC(3,12,1) = 1(m - 2n)
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás